دراسة إستشرافية لدور الصكوك الإسلامية السيادية في تمويل العجز الموازني في الجزائر على ضوء تجارب دولية - شيكور سارة (جامعة البليدة2-كلية العلوم الإقتصادية والعلوم التجارية وعلوم التسيير, 2024)
تيدف ىذه الدراسة الى إبراز دور الركهك الاسلامية الديادية في مهاجية العجز السهازني في الجزائر، من خلال الاستفادة من دراسة تجارب بعض الدول الرائدة في مجال صشاعة الركهك الاسلامية واستخداميا من طرف حكهمات ىذه الدول لتغظية الشفقات العامة وتسهيل السذاريع التشسهية، خاصة الستعمقة مشيا بالبشية التحتية. وقد تم الاعتساد عمى السشيج التحميمي وذلك من أجل تحميل حجم نسه وتظهر سهق الركهك الاسلامية في العالم وتدميط الزهء عمى أكثر الدول السردرة لمركهك الاسلامية، بالإضافة إلى تحميل مؤشرات العجز في السهازنة العامة في الجزائر والأسباب التي أدت الى تزايد ىذا العجز خلال الدشهات الأخيرة، كسا قسشا بهضع ترهر لكيفية تفعيل الركهك الاسلامية في الج ازئر لمتخفيف من حدة العجز السهازني الذي تعاني مشو الجزائر. تهصمت ىذه الدراسة إلى أن الركهك الاسلامية الديادية بديل تسهيمي فعال لأدوات الدين التقميدية تداىم في الحد من العجز السهازني في الجزائر، وذلك من خلال تسهيميا للإنفاق ىستيا مدا الاستثساري في السهازنة العامة بدل الاعتساد عمى الاي اردات الشفظية فقط، بالإضافة الى في جذب السدتثسرين السيتسين بالتسهيل الاسلامي لمجزائر الذي بدوره سيداىم في تهفير العسمة الأجشبية، زيادة ندب العسالة وتحقيق التشسية الاقترادية، ويتهقف نجاحيا في الجزائر عمى مدى قهى ومتانة القهانين والتذريعات السشظسة لعسل الركهك الاسلامية. الكلمات المفتاحية: صكهك إسلامية سيادية؛ عجز مهازني؛ تجارب دولية؛ قانهن الركهك الإسلامية؛ تسهيل إسلاميAbstract: This study aims to highlight the role of sovereign Islamic bonds in addressing the budgetary deficit in Algeria by drawing on the experiences of some leading countries in the field of Islamic bonds industry and their utilization by the governments of these countries to cover public expenses and finance developmental projects, particularly those related to infrastructure. Analytical and descriptive methods were employed to analyze the growth and development trends of the global Islamic bonds market and shed light on the leading issuers of Islamic bonds. Additionally, the study examined the deficit indicators in Algeria's general budget and the reasons behind its increase in recent years. A conceptual framework was developed for activating Islamic bonds in Algeria to mitigate the severity of the budgetary deficit faced by the country. This study concludes that sovereign Islamic bonds serve as an effective financial alternative to traditional debt instruments, contributing to reducing the fiscal deficit in Algeria. They achieve this by financing investment expenditures in the general budget, replacing reliance solely on oil revenues. Furthermore, these bonds attract investors interested in Islamic financing for Algeria, which, in turn, will help in foreign currency reserves, increase employment rates, and promote economic development. The success of Islamic bonds in Algeria depends on the strength and robustness of the laws and regulations governing the operation of Islamic bonds. Keywords: Sovereign Islamic bonds, budgetary deficit, international experiences, Islamic bonds law, Islamic financing
Keywords: السيادة الإسلامية; التجارب; العجز; الإستشراف; العجز في الجزائر